1988
DOI: 10.1111/j.1476-5381.1988.tb11485.x
|View full text |Cite
|
Sign up to set email alerts
|

Modification by steroids of pulmonary oedema and prostaglandin E2 pharmacokinetics induced by endotoxin in rats

Abstract: 1 A single i.p. injection of bacterial endotoxin in rats (3.5 mg kg ')caused lung injury assessed as changes in lung dry: wet weight ratio and leukopaenia over the subsequent 28 h.2 This treatment also slowed the efflux of 14C from [14C]-prostaglandin E2 (PGE2), i.e., increased t112 and increased the survival of PGE2 in isolated perfused lungs over the same period. 3 These effects of endotoxin were reversed by methylprednisolone (30mgkg 1), given 30min after the endotoxin. 4 Another synthetic corticosteroid, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
2001
2001

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…It has also been shown that a single bolus of PGE 2 perfused through isolated lungs results in the recovery of 15%, i.e. in the order of 85% of the PGE 2 is metabolized after a single pass through the lungs [17]. In the present study the amount recovered in CSF samples was up to 0.5% of that given systemically into the marginal ear vein.…”
Section: Discussionmentioning
confidence: 67%
“…It has also been shown that a single bolus of PGE 2 perfused through isolated lungs results in the recovery of 15%, i.e. in the order of 85% of the PGE 2 is metabolized after a single pass through the lungs [17]. In the present study the amount recovered in CSF samples was up to 0.5% of that given systemically into the marginal ear vein.…”
Section: Discussionmentioning
confidence: 67%